2017
DOI: 10.1044/2016_ajslp-16-0071
|View full text |Cite
|
Sign up to set email alerts
|

Discourse Characteristics in Aphasia Beyond the Western Aphasia Battery Cutoff

Abstract: Individuals with aphasia who score above the WAB-R Aphasia Quotient cutoff demonstrate discourse impairments that warrant both treatment and special attention in the research literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 25 publications
5
40
0
Order By: Relevance
“…Recent evidence suggests individuals with WAB‐R AQ > 93.8 (no aphasia) frequently present with subtle discourse deficits regardless of their normal WAB‐R AQ (Fromm et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Recent evidence suggests individuals with WAB‐R AQ > 93.8 (no aphasia) frequently present with subtle discourse deficits regardless of their normal WAB‐R AQ (Fromm et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…For example, a patient may report language difficulties suggesting presence of aphasia, but scores are at or above the diagnostic cutoff on the WAB-R. Fromm et al recently shed light on the importance of capturing subtle language deficits in these patients, indicating that standardized test batteries are not sensitive to subtle linguistic deficits that can affect discourse-level language production. 67 Returning back to Dalton and Richardson's study, 54 omnibus median test demonstrated that core lexicon measures differed the control group from all aphasia subtypes, including those who have had a stroke but are not aphasic by WAB (NABW; N ¼ 25). The core lexicon measure also differed between the NABW and persons with anomic (p ¼ 0.002), conduction (p < 0.001), and Wernicke's aphasia (p < 0.001) groups.…”
Section: Considerations For Assessmentmentioning
confidence: 96%
“…32 Additionally, a formula for converting codes into scores has been developed by Kong, 56 and modified by Richardson and Dalton. 6 MCA is sensitive to differences between clinical and control populations, 32,[56][57][58][59][60][61] and correlates with listeners' perceptions. 62 Additionally, while different measures have been used (e.g., tau, absolute agreement), all investigations reporting reliability show adequate inter-and intra-rater reliability.…”
Section: Main Concept Analysismentioning
confidence: 99%
“…Crucially, AC efficiency and CoreLex scores are sensitive enough to detect differences between healthy controls and those who score above the cut-off for a diagnosis of aphasia, consistent with Fromm and colleagues. 58 Combined with previous research reporting changes in similar informativeness measures in response to treatment, [81][82][83][84][85] and their relationship to measures of quality of life, 62,81 these results suggest that MCA, CoreLex, and derived efficiency scores are informative discourse measures with standardized administration and accompanying normative data 6,32,40,56,57,[59][60][61]64,65 that may be appropriate for use as primary clinical outcomes as defined by Brady et al 2 Primary Progressive Aphasia This is the first study to examine discourse informativeness, typicality, and efficiency in adults with PPA. Individuals with PPA produce discourse that is less informative and efficient, with fewer typical lexical items than healthy controls.…”
Section: Stable Aphasiamentioning
confidence: 99%